Pemanfaatan Media Flashcard dalam Meningkatkan Kemampuan Keterampilan Membaca pada Pelajaran Bahasa Indonesia - Tsalitsatul Maulidah (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2020)
One of the Indonesian language skills which according to students is very difficult to do is reading skills. So this study aims to determine the benefits of student reading skills using a flashcard. In this study using classroom action research methods carried out through 2 cycles with each cycle stages are planning, action, observation and reflection. The research data were obtained through classroom observations and tests. The results showed an increase in reading ability of grade 1 elementary school students using flashcard media, visible reading ability of students has increased every cycle, namely in the pre-cycle there are 5 students or 25%, an increase in cycle I of 10 students or 50% and at the end of the second cycle to 18 students or 90% complete.